Syntax of Dutch : Adpositions and Adpositional Phrases - Broekhuis, Hans, 1959- (Book collections on Project MUSE., 2013)
The Syntax of Dutch' will be published in at least seven volumes in the period 2012-2016 and aims at presenting a synthesis of the currently available syntactic knowledge of Dutch. It is primarily concerned with language description and not with linguistic theory, and provides support to all researchers interested in matters relating to the syntax of Dutch, including advanced students of language and linguistics. The volume 'Adpositions and Adpositional Phrases' discusses the internal make-up and the distribution of adpositional phrases. Topics that are covered include complementation and modification of adpositional phrases, as well as their predicative, attributive and adverbial uses. A separate chapter is devoted to the formation and the syntactic behavior of pronominal PPs like erop 'on it, which also includes a more general discussion of the syntax of so-called R-words like er 'there'.